Analysis of The Need for Teaching Modules Based on Local Wisdom in Sidoarjo - Ningsih, Fitriya; Ummah, Fiena Saadatul; Rachmadyanti, Putri; Mariana, Neni (Journal of Learning Improvement and Lesson Study, 2025)
Sidoarjo Regency has diverse local wisdom. However, the educational potential has not been utilized optimally. This research aims to (1) identify and map the types of local wisdom of Sidoarjo that have the potential to be integrated into learning; (2) Analyzing the perception and needs of teachers and students for teaching modules based on local wisdom; and (3) Formulate an outline of the characteristics of effective teaching modules. The method uses qualitative research of the type of case study at SD Negeri Waru 1 Sidoarjo. Observation, interview, and documentation data collection techniques. Data is analyzed through data reduction, data presentation, and conclusion drawn. The results of the study revealed that: (1) There are five pillars of local wisdom in Sidoarjo that have great potential as a source of learning, namely customs, culinary, dance, historical sites, and batik; (2) Teachers experience difficulties in integrating local wisdom due to the limited systematic and applicative teaching modules, while students crave contextual learning that can foster cultural pride; and (3) Teaching modules with thematic-integrative characteristics are needed, using a project-based learning approach, and equipped with LKPD and interesting audiovisual materials.